Can Patient Frailty Be Estimated from Inpatient Records? A Prospective Cohort Study. Issue 1 (2020) - Marincowitz, Carl; Turner, Victoria; Allgar, Victoria; Bellwood, Jodie; Wheeler, Alice; Hale, Matthew; Callaghan, Harriet; Clegg, Andrew; Sheldon, Trevor A.
No abstract available